Analysis of the Impact of Climate Change on National Vulnerability Based on Fuzzy Comprehensive Evaluation. (13th August 2020) - Zhu, Jia-Ming; Chen, Yang; Zhang, Su
Abstract : Climate change has become one of the major threats to global security. On the impact of climate change on national vulnerability, the researchers firstly select relevant factors and data and analyze the principal components to determine the weight of climate change on vulnerability so as to analyze the impact of climate change on national vulnerability. Secondly, based on the influencing factors, we obtain the national vulnerability score through the fuzzy comprehensive evaluation method, delineate the impact scope according to the score, and predict climate change by means of regression analysis and time series analysis. Finally, according to the characteristics of cities and continents, the model is revised, a PSR model and a cluster analysis model are established, and the prediction accuracy is improved.